ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN DENGAN STRATEGI MENGAJAR GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN PPKn DI SMP SWASTA KRISTEN BNKP TELUK DALAM - Sabaati Waruwu (Universitas Nias Raya, 2023)
The current development of science and technology requires teachers to be able to follow developments in these aspects. Likewise, in learning activities teachers are required to create interesting learning by using learning media to increase students' interest in learning in the learning process. The aims of this research are 1) to determine the use of learning media with teaching strategies by teachers in class VIII in Civics subjects at BNKP Teluk Dalam Christian Private Middle School and 2) to determine the increase in students' interest in learning in the use of learning media with teaching strategies by teachers in class VIII in Civics subject at BNKP Teluk Dalam Christian Private Middle School. This type of research is qualitative research using a descriptive approach. The subjects in this research were class VIII PPKn subject teachers and class VIII students of BNKP Teluk Dalam Christian Private Middle School. Data collection techniques in this research used 1) Observation Techniques, 2) Interview Techniques, 3) Documentation Techniques. The data analysis technique in this research uses 1) Data Reduction, 2) Data Display 3) Conclusion Drawing. The results of this research indicate that there is an increase in students' interest in learning through the use of learning media with teachers' teaching strategies. So it can be concluded that 1) The use of learning media with teaching strategies for teachers in class VIII in Civics subjects at BNKP Teluk Dalam Christian Private Middle School uses learning media in the teaching and learning process. 2) Increasing students' interest in learning about the use of learning media with the teaching strategies of teachers in class VIII on Civics subjects at BNKP Teluk Dalam Christian Private Middle School. Students become more active in learning, do assignments well, take complete notes, answer questions given and listen when the teacher explains. Suggestions from researchers are 1) Teachers should use learning media with teaching strategies in the learning process so that they can increase students' interest in learning in the teaching and learning process, 2) Students should always be active in learning activities and always foster interest in learning by involving themselves in the learning process